Three R’s: reduce, recycle and reuse; Kathmandu Medical College: An eco-friendly hospital - Rijal, Rika (Journal of Kathmandu Medical College, 2017)
Not available. Journal of Kathmandu Medical College Vol. 5, No. 3, Issue 17, Jul.-Sep., 2016, Page: 75-76